POLA DISTRIBUSI HUJAN DAN PENGARUHNYA TERHADAP PENYIMPANGAN HIDROGRAF BANJIR DAS JANGKOK - HUMAIRO SAIDAH; M. BAGUS BUDIANTO; I WAYAN YASA; ERY SETIAWAN (Universitas Mahasaraswati K. Mataram, 2023)
Determining the rain pattern distribution is believed to affect the design flood. Providing hourly rainfall observations can be obtained, and the distribution patterns can be determined. However, in areas that do not have one, flood discharge calculations are carried out by distributing daily rainfall using empirical methods. This study distributes daily rainfall into hourly rainfall in the Jangkok watershed using ABM and Mononobe methods and calculates the flood hydrograph using the Nakayasu model. The synthetic unit hydrograph obtained from the actual rain distribution is then compared with the unit hydrograph generated from the empirical distribution, then the deviation is measured. The results showed that the Mononobe and ABM rain distribution gave the same hydrograph shape as the observation one, only for 2 hours of rain duration. As long as the rain lasts 3-6 hours, the peak flood discharge (Qp) tends to be lower, 7-20% for Mononobe and 2-7% for ABM. Then the Qp becomes overestimated (5-12%) for a rain duration of >6 hours. Mononobe gives the same flood peak time (Tp) as observation rain for 1-5 hours rain duration and becomes 1 hour earlier for >6 hours. In contrast, ABM produces peak times 1 hour longer than hydrographs with observation rain. Generally, the two methods provide a more significant hydrograph deviation for a longer duration of rain.